Fertilization mechanism - Bellido, Percy (2015)
The traditional definition indicates that fertilization is a process of union of the male and female pronuclei for the formation of a new being. It is not just the penetration of a small cell (sperm) in a large (oocyte). It is an intercellular interaction, highly specialized, in which an active gamete other.